ANALYSIS OF THE INFLUENCE OF ENTREPRENEURSHIP LEARNING ON ENTREPRENEURIAL READINESS OF CULINARY MANAGEMENT STUDENTS - Arina Luthini Lubis; Frangky Silitonga; Wahyudi Ilham (Prima Magistra: Jurnal Ilmiah Kependidikan, 2025)
Entrepreneurship education plays a crucial role in preparing vocational graduates not only to become job seekers but also to become job creators. This study aims to analyze the effect of entrepreneurship learning on the entrepreneurial readiness of students in the Culinary Management Study Program. A quantitative method was employed using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) approach, involving 22 students enrolled in the Entrepreneurship course. The research instrument was a structured questionnaire comprising valid and reliable indicators, tested through outer loading analysis, Average Variance Extracted (AVE), and Composite Reliability (CR). The results show that entrepreneurship learning has a very strong and significant influence on students’ entrepreneurial readiness, with a path coefficient of 0.921 and an R-square value of 0.848. These findings indicate that a contextual, experience-based, and practical learning approach is effective in shaping students' preparedness to initiate culinary businesses. The study concludes that well-designed and well-implemented entrepreneurship education significantly contributes to students’ readiness to enter the business world. This research recommends enhancing the quality of entrepreneurship learning through industry collaboration, real business projects, and sustainable mentoring programs.